Socialization of gifted children: problems and prospects of research - Kozyreva, M. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
Іn this article features socialization as such, problems and peculiarities of its passage gifted children. We have identified and the basic problems of socialization gifted children and conducted data analysis aspects in order to develop further lines of research this subject.